Pelatihan Teknik Pengemasan Pupuk Organik Cair dan Pestisida Nabati untuk Menjaga Viabilitas Bakteri Pada Kelompok Seraton di Desa Tonasa - A Dwi Wahyuni P; Nur Ihwan Safutra (PT.Mantaya Idea Batara, 2022)
The Seraton Farmer Group is a group of mineral farmers in Tonasa Village, Sanrobone District, Takalar Regency. Located 44-45 KM from Makassar City, with an area of ??384 KM2. Tonasa village has topographic characteristics as a lowland area surrounded by plantations such as rice, corn, chili, and others, with an average air temperature during the day between 35°C and at night between 20° - 25°C. The Seraton Farmer Group processes natural ingredients into liquid organic fertilizers and vegetable pesticides as an effort to overcome the exposure of chemicals to plants. To prevent liquid organic fertilizers and vegetable pesticides from spoiling quickly, it is very important to store liquid fertilizers and vegetable pesticides in dry and tightly closed storage. This PKM provides learning and training on packaging techniques for Liquid Organic Fertilizers and Vegetable Pesticides. The method used is socialization followed by training on the packaging of liquid organic fertilizers and vegetable pesticides. The result of this service is an increase in knowledge and skills about the benefits and good and correct techniques to maintain bacterial viability.